2018
DOI: 10.3390/w10060714
|View full text |Cite
|
Sign up to set email alerts
|

Water Event Categorization Using Sub-Metered Water and Coincident Electricity Data

Abstract: This study evaluated the potential for data from dedicated water sub-meters and circuit-level electricity gauges to support accurate water end-use disaggregation tools. A supervised learning algorithm was trained to categorize end-use events from an existing database consisting of features related to whole-home and hot water use. Additional features were defined based on dedicated irrigation metering and circuit-level electricity gauges on major water appliances. Support vector machine classifiers were trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…First, there is an inverse correlation between the dataset size (or the time series length) and the time sampling resolution. Datasets comprising hundreds or thousands of homes (e.g., [48,49,[64][65][66]) generally include data collected with a monthly or daily time sampling resolution, while datasets with a sub-daily time sampling resolution only include a few units or tens of homes (e.g., [67][68][69]). This may be attributed to the experimental extent of most high-resolution studies, their usually short-term duration, and the costs of deploying large-scale smart metering systems.…”
Section: Dataset Spatial Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is an inverse correlation between the dataset size (or the time series length) and the time sampling resolution. Datasets comprising hundreds or thousands of homes (e.g., [48,49,[64][65][66]) generally include data collected with a monthly or daily time sampling resolution, while datasets with a sub-daily time sampling resolution only include a few units or tens of homes (e.g., [67][68][69]). This may be attributed to the experimental extent of most high-resolution studies, their usually short-term duration, and the costs of deploying large-scale smart metering systems.…”
Section: Dataset Spatial Scalesmentioning
confidence: 99%
“…The distribution of the end use datasets in Figure 5 is an empirical validation of the findings of a previous study by Cominola et al [28], which demonstrated that only data gathered with time sampling resolutions of a few seconds or, at most, 1 min, can be used to accurately estimate the contribution, peak, and time of use of individual water fixtures, especially when multiple end uses are active. Besides facilitating accurate end use disaggregation [67][68][69][156][157][158], such high resolution data also allow a detailed characterization of consumer behaviors [77,155,159,160], and the design of customized water demand strategies [88,123,142,161,162].…”
Section: Dataset Temporal Scalesmentioning
confidence: 99%
“…pressure data) have been proposed as well (e.g. Kim et al 2008;Froehlich et al 2009Froehlich et al , 2011Srinivasan et al 2011;Ellert et al 2015;Vitter and Webber 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Despite the number of algorithms described in the literature, opportunities to replicate or build from these tools are limited due to the unavailability of code and/or data. Di Mauro et al (2020) found that, of 41 data sets collected for assessing end uses of water at residential properties, only four (Beal and Stewart 2011;Makonin 2016;Vitter and Webber 2018;Kofinas et al 2018) had an open access policy. In limited instances, flow trace data (i.e., the raw, high resolution data collected) and event files (i.e., end use events and their attributes extracted from raw data) from past studies were available for purchase (Aquacraft 2016), including the events table resulting from the one of the largest studies of water end uses conducted to date (DeOreo et al 2016).…”
Section: Introductionmentioning
confidence: 99%